Photocatalysis of dyes: operational parameters, mechanisms, and degradation pathway - Tan, Shi Nin; Lian, Yuen Mei; Ros Azlinawati, Ramli (Elsevier B.V., 2025)
Photocatalysis is an advanced oxidation process (AOP) that has significant attention to the degradation of organic pollutants. Although most literature on photocatalysis mainly focuses on the basic photocatalytic mechanisms, photocatalyst designs, and operational parameters, this research aims to delve deeply into the various process parameters and mechanisms under different conditions. It explores intermediates produced by dye photocatalysis and the proposed degradation pathways. This review systematically analysed relevant literature based on various databases, studying various process parameters and mechanisms as well as utilising analytical techniques (spectroscopy and chromatography) to synthesise key themes and findings in photocatalysis. This review revealed significant advancements in photocatalysis, highlighting the photocatalytic process has 4 domain steps in degradation pathways, including demethylation, ring shortening, ring opening, and mineralisation. Previous studies indicated the emergence of new peaks at 331 nm and 370 nm in UV-Vis analysis for MB, while hypsochromic shifts for RhB were attributed to the processes of demethylation and de-ethylation, respectively. In short, this review underscores the potential of dye photocatalysis to revolutionise green analytical practices and emphasises the importance of sustainable approaches in analytical methodologies, focusing on innovative and eco-friendly analytical methods aligned with the scope of the journal.